Solar powered warning street lamp - Mohd Fitri, Mohd Sariff (2008)
This project focuses on warning street lamp. Warning street lamp is a device with flashing lamp and it will be place at certain road. The function of the warning lamp is to remind people about there are hazard at the road such as an emergency happen. Besides, it is can be used at the construction road. This project is better because it uses the solar energy. This lamp does not need the electrical power and it can be placed at rural area that does not have electricity supply. This lamp have three different functions which are a blinking lamp in a circle shape, a warning lamp in right arrow shape and a warning lamp in left arrow shape. Those three warning lamp can be changed manually by pressing the push button at the control circuit. The right and left shape warning lamp is important because of it can show the road ahead which is to turn right or left especially when driving at night. Hope that this project can reduce the accident at the road.